A new Mapinguari Papavero & Wilcox (Diptera, Mydidae, Mydinae) from Minas Gerais State, Brazil - Calhau, Julia; Lamas, Carlos José Einicker; Nihei, Silvio Shigueo (Zootaxa, 2016)
Mapinguari Papavero & Wilcox, 1974 (Diptera, Mydidae, Mydinae) is a very rare monotypic genus, with the type-species, M. politus (Wiedemann, 1828), occurring exclusively in Amazonia. With the description of Mapinguari uai sp. nov. from a remnant of the Atlantic Forest in southeastern Brazil, the distribution of the genus is greatly expanded. In addition, an updated diagnosis for the genus and its type-species is provided.